Inhibition of Macrophage Migration Inhibitory Factor Protects against Inflammation and Matrix Deposition in Kidney Tissues after Injury - Hong Lu; Yongyu Bai; Lianfeng Wu; Weilong Hong; Yong Liang; Bicheng Chen; Yongheng Bai (Mediators of Inflammation)
Background. Macrophage migration inhibitory factor (MIF) is an important immunoregulatory cytokine involved in inflammation, which may be one important reason resulting in matrix deposition in renal tissues after injury. However, the underlying mechanisms have not yet been elucidated. Methods and Results. We uncovered a crucial role of MIF in inflammation and collagen deposition in vivo and in vitro. In rats, ureteral obstruction induced tubular injury, matrix accumulation, and inflammatory cell infiltration. Additionally, enhanced MIF levels in the obstructed kidneys were closely related to the increasing numbers of CD68-positive macrophages. These obstruction-induced injuries can be relieved by recanalization, consequently resulting in downregulated expression of MIF and its receptor CD74. Similarly, ischemia reperfusion induced renal injury, and it was accompanied by elevated MIF levels and macrophages infiltration. In cultured tubular epithelial cells (TECs), aristolochic acid (AA) promoted matrix production and increased MIF expression, as well as the release of macrophage-related factors. Inhibition of MIF with an antagonist ISO-1 resulted in the abolishment of these genotypes in AA-treated TECs. Conclusion. MIF plays an important role in macrophage-related inflammation and matrix deposition in kidney tissues following injury. MIF as a specific inhibitor may have therapeutic potential for patients with inflammatory and fibrotic kidney diseases.